2006
DOI: 10.1182/blood-2005-09-3620
|View full text |Cite
|
Sign up to set email alerts
|

Combined deficiency of factor V and factor VIII is due to mutations in either LMAN1 or MCFD2

Abstract: Mutations in LMAN1 (ERGIC-53) or MCFD2 cause combined deficiency of factor V and factor VIII (F5F8D). LMAN1 and MCFD2 form a protein complex that functions as a cargo receptor ferrying FV and FVIII from the endoplasmic reticulum to the Golgi. In this study, we analyzed 10 previously reported and 10 new F5F8D families. Mutations in the LMAN1 or MCFD2 genes accounted for 15 of these families, including 3 alleles resulting in no LMAN1 mRNA accumulation. Combined with our previous reports, we have identified LMAN1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
121
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(130 citation statements)
references
References 23 publications
6
121
0
3
Order By: Relevance
“…So far, only two missense mutations have been reported in LMAN1, p.Met1Thr, and p.Cys475Arg, which resulted in little or no LMAN1 protein in the cells [13,15]. In this report, we showed that lymphoblasts from a patient with a homozygous p.Trp67Ser mutation possessed a variant LMAN1 protein in the same amount as LMAN1 in lymphoblasts from a normal individual.…”
Section: Discussionsupporting
confidence: 51%
“…So far, only two missense mutations have been reported in LMAN1, p.Met1Thr, and p.Cys475Arg, which resulted in little or no LMAN1 protein in the cells [13,15]. In this report, we showed that lymphoblasts from a patient with a homozygous p.Trp67Ser mutation possessed a variant LMAN1 protein in the same amount as LMAN1 in lymphoblasts from a normal individual.…”
Section: Discussionsupporting
confidence: 51%
“…Genetic mutations in LMAN1 account for approximately 70% of F5F8D families, whereas the remaining 30% families possess mutation in MCFD2 (3,4). LMAN1 encodes the transmembrane lectin ERGIC-53 (ER-Golgi intermediate compound protein of 53 kDa) (5), which possesses a luminal carbohydrate recognition domain (CRD) with specificity for highmannose-type oligosaccharides (6,7) and forms dimers or hexamers stabilized by disulfide bonds formed in its stalk domain (5,8).…”
mentioning
confidence: 99%
“…Whereas the above disorders affect the sorting signal on the cargo, proteins acting as cargo receptors are defective in a bleeding syndrome, combined deficiency of coagulation factors V and VIII. In this, the inclusion of the two coagulation factors into ER-Golgi carriers, and thus their secretion, is hampered by defects in ERGIC-53, a mannose-binding lectin that executes a cargo-sorting function in ER-to-Golgi trafficking (Nichols et al, 1998), or its binding partner, multiple coagulation factor deficiency protein 2 (MCFD2) (Zhang et al, 2003;Zhang et al, 2006). The patients have normal plasma concentrations of other proteins, which suggests that the Ca 2+ -dependent ERGIC-53-MCFD2 complex has a specific function in sorting of a subgroup of glycoproteins that are transported out of the ER (Zhang et al, 2005).…”
Section: Journal Of Cell Science 119 (24)mentioning
confidence: 99%